Throughfall Reduction × Fertilization: Deep Soil Water Usage in a Clay Rich Ultisol Under Loblolly Pine in the Southeast USA - Qi, Ji; Markewitz, Daniel; McGuire, Mary Anne; Samuelson, Lisa; Ward, Eric (Frontiers in Forests and Global Change, 2020)
Forests in the Southeast USA are predicted to experience a moderate decrease in precipitation inputs over this century that may result in soil water deficiency during the growing season. The potential impact of a drier climate on the productivity of managed loblolly pine (Pinus taeda L.) plantations in the Southeast USA is uncertain. Access to water reserves in deep soil during drought periods may help buffer these forests from the effects of water deficits. To better understand the potential impact of drought on deep soil water, we studied the combined effects of throughfall reduction and fertilization on soil water usage of a clay rich Piedmont Ultisol to a depth of 3 m in a 6-year-old loblolly pine plantation by applying a throughfall reduction treatment (ambient versus ~30% throughfall reduction) and a fertilization treatment (no fertilization versus fertilization). Throughfall reduction lowered soil moisture for all depths and differences were significant in the surface soils (0-0.3 m) (1.2-3.6%) and deep soils (below 2 m) (2.6-3.6%). Fertilization also lowered soil moisture for all depths and differences were significant at 0.3-0.6 m (2.9%) and 1.94-3.06 m (4.5%). Fertilization when combined with the throughfall reduction treatment significantly decreased soil water at 0.1-0.9 m depth. Soils of all depths were rarely depleted of plant available water with the exception of 0-0.1 m, mainly during the growing season. Under throughfall reduction treatment, soil below 0.9 m consistently accounted for more than half of the change in plant available water during months when transpiration exceeded precipitation. When considering the whole soil profile in this clay rich Ultisol, soil water storage buffered transpirational demand in the face of increasing dryness.